Enhancing the functional output of transplanted islets in diabetic mice using a drug-eluting scaffold - Zhu, Kelei (J Biol Eng, 2018)
BACKGROUND: Islet transplantation is increasingly used in the diabetic patients to control the blood glucose level. However, the functional output of transplanted islets remains hampered due to the local inflammation, loss of islets, etc. To that end, in this study we explored to enhance the functional output of transplanted islets in diabetic mice by employing a drug-eluting scaffold with a payload of interleukin 4 (IL-4). RESULTS: According to the in vitro studies, the scaffold showed no cytotoxicity, a rapid release of IL-4 within a week and the IL-4 retained its bioactivity. During the 4-week time window after the islet transplantation, in vivo studies showed that the levels of blood insulin and C-peptide 2 in diabetic mice in the drug-eluting scaffold group significantly increased since week 2, which effectively reduced the blood glucose level. In addition, these mice demonstrated a stronger capability to withstand a rapid glucose spike as evidenced by the tolerance of sudden oral glucose challenge test result. A further mechanistic study suggested that the enhanced functional output could be attributed to the M2 polarization of macrophages as evidenced by the increase of CD163(+)/CD68(+) macrophages in the islet tissues. A M2 polarization of macrophages is widely believed to exert an anti-inflammatory influence on local tissues, which could accelerate the resolution of local inflammation following the islet transplantation. CONCLUSION: Our study shed a new light on the hyperglycemia management of diabetic patients following the islet transplantation.